TEG®- or ROTEM®-based individualized goal-directed coagulation algorithms: don’t wait - act now - Spahn, Donat R (Critical care (London, England), 2014)
In trauma patients, TEG ® and ROTEM ® allow prediction of massive transfusion requirement and mortality, and creation of goal-directed, individualized coagulation algorithms that may improve patient outcome. This outcome benefit has been shown for cardiac surgery in prospective randomized trials. For trauma, only non-randomized studies have been performed. Nevertheless, TEG ® and ROTEM ® are highly promising monitoring techniques to guide coagulation management in all types of major bleeding, including trauma.